Financial burden due to non-compliance of ultrasound with national standards in pregnant women with low-risk pregnancy covered by the health centers of Isfahan, 2019 - Raziye Pourkazemi; Mahsa Shaali; Reza Rezayatmand (Mashhad University of Medical Sciences, 2022)
Background and Aim: Non-compliance of pregnancy and childbirth care with national guidelines and standards incur a huge financial burden on health system. This study aimed to estimate the financial burden of ultrasound screening for low-risk pregnant women which is not in accordance with national standards.Methods: This was a cross-sectional study in which 230 pregnant women with low-risk pregnancies, getting care in comprehensive health centers, were assessed in terms of the number of ultrasounds they had during their pregnancy and to see how it would be in accordance with national standards. The financial burden was estimated based on the total fertility rate per year from the perspective of health insurance as well as patients.Results: The average number of ultrasounds performed in pregnancy per person was 5 times (4 one-dimensional ultrasound and one three-dimensional ultrasound), which is almost twice the defined level of the national standard (3 one-dimensional ultrasound). It was estimated that this imposed a financial burden of about 364,707,521,587 Rials on basic insurers. Also, individuals incur a financial burden of about 2,898,188,006,140 Rials. It meant that following national standard for performing ultrasound examination during low-risk pregnancy would have saved 3260 billion IRR for Iranian health system.Conclusion: Non-compliance of ultrasound services with national standards is associated with several effects such as imposing additional costs on the family and insurance organizations. Following national standards for prenatal care would stop providing unnecessary services during pregnancy and reduce related costs which would be beneficial both for pregnant women and health system.